Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12223-017-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Severity of drug resistance and co-existence of Enterococcus faecalis in diabetic foot ulcer infections

Abstract: The genes encoding aminoglycoside resistance in Enterococcus faecalis may promote collateral aminoglycoside resistance in polymicrobial wounds. We studied a total of 100 diabetic foot ulcer samples for infection and found 60 samples to be polymicrobial, 5 to be monomicrobial, and 35 samples to be culture negative. A total of 65 E. faecalis isolates were screened for six genes coding for aminoglycoside resistance, antibiotic resistance patterns, and biofilm production. Infectious Diseases Society of America/Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…All of the studied isolates were also negative for aph(2′′)-Ib, aph(2′′)-Ic, aph(2′′)-Id, and ant(4′)-Ia genes amplification. Absence of the aph(2′′)-Ib, aph(2′′)-Ic, and aph(2′′)-Id genes in E. faecalis strains was shown in several studies [34][35][36][37]. They are minor contributors to gentamicin resistance among Enterococcus strains [33].…”
Section: Discussionmentioning
confidence: 97%
“…All of the studied isolates were also negative for aph(2′′)-Ib, aph(2′′)-Ic, aph(2′′)-Id, and ant(4′)-Ia genes amplification. Absence of the aph(2′′)-Ib, aph(2′′)-Ic, and aph(2′′)-Id genes in E. faecalis strains was shown in several studies [34][35][36][37]. They are minor contributors to gentamicin resistance among Enterococcus strains [33].…”
Section: Discussionmentioning
confidence: 97%
“…These biofilms are commonly resistant to topical and systemic antibiotics, which reduces the effectiveness of the antimicrobial treatment. For instance, Shettigar et al found the authors showed that 60% of the DFU samples investigated were infected with polymicrobial biofilms, in which the isolated E. faecalis showed higher resistance to antibiotics than non-biofilm grown cells (213). Furthermore, bacteria within biofilms produce several protective components.…”
Section: Antibioticsmentioning
confidence: 99%
“…All E. faecalis isolated showed high levels of sensitivity to the different antibiotic classes. Shettigar et al, 12 in a prospective epidemiological study with 100 patients, found E. faecalis with high rates of resistance to antibiotics such as erythromycin (94%), tetracyclines (91%) and ciprofloxacin (89%). In the present study 165 aerobic organisms isolated.…”
Section: Resultsmentioning
confidence: 99%